Taxonomic Identification of Selected Seaweeds from the Jarjar Oma Coast and Quantitative Determination of Chlorophyll and Carotenoid Pigments - Hamida EL. Elsalhin; Hanan M. Abobaker; Wedad El. Moftah (African Journal of Advanced Pure and Applied Sciences, 2026)
Marine macroalgae (Seaweeds) are important components of coastal ecosystems and play a significant role in primary production and biodiversity. This study aimed to identify seaweed species from the Jarjar Oma coast, Libya, and evaluate their photosynthetic pigment content. Seaweed samples were manually collected at different time points between May and August 2024 to account for seasonal variation. Species identification was carried out using morphological and anatomical characteristics, supported by microscopic examination and taxonomic references. A total of 12 species belonging to 10 genera were identified. The recorded species were classified into three major algal groups: Chlorophyta (50%), Phaeophyta (25%), and Rhodophyta (25%). The genus Cystoseira was the most dominant throughout the study period. Pigment analysis showed significant variation among species. Ulva lactuca exhibited the highest concentrations of chlorophyll a (20.435 µg/mg) and chlorophyll b (18.173 µg/mg), whereas Cystoseira barbata recorded the highest carotene content (8.817 µg/mg). Red algae, including Laurencia papillosa and Jania rubens, showed comparatively lower pigment concentrations. These differences reflect adaptations to varying environmental conditions, particularly light availability and habitat depth. The findings provide baseline information on the diversity and physiological characteristics of marine macroalgae along the Libyan Mediterranean coast and may support future ecological and biotechnological studies.